Peritoneal dialysis as an urgent-start option for incident patients on chronic renal replacement therapy: World experience and review of literature - Bittencourt Dias, Dayana [UNESP]; Mendes, Marcela Lara [UNESP]; Alves, Camila Albuquerque [UNESP]; Caramori, Jacqueline Teixeira [UNESP]; Ponce, Daniela [UNESP] (Karger Publishers, 2020)
Chronic kidney disease is a significant problem of public health worldwide, and up to 60% of patients start dialysis in an unplanned manner without a definitive dialysis access. Recently, peritoneal dialysis (PD) has emerged as an alternative to unplanned chronic dialytic method, and the world collective experience shows that PD can be an efficient, safe, and cost-effective alternative with comparable outcomes to the planned PD and urgent-start hemodialysis (HD). More importantly, as compared to urgent-start HD using a central venous catheter, urgent-start PD has significantly fewer incidences of catheter-related bloodstream infections, dialysis-related mechanical complications, and need for dialysis catheter reinsertions during the initial time of the therapy. An integrative review was conducted on PD urgent start compared to HD urgent start and to planned PD, identifying its potential advantages and limitations. Literature search was performed within multiple databases, and observational studies on clinical experience with urgent PD were reviewed and appraised.
Keywords: Chronic kidney disease; Hemodialysis; Mortality; Peritoneal dialysis; Urgent start